高炉水砕スラグの粒度および密度に及ぼす製造条件の影響 - 後藤, 滋明; 桑山, 道弘; 渡辺, 圭児; 後藤, 弘樹; 當房, 博幸; 田中, 敏宏 (鉄と鋼, 2014)
The water granulation conditions for producing high density, coarse granulated blast furnace slag were investigated in a laboratory-scale experiment. The influence of the slag temperature, water temperature and nozzle shape on the density and grain size of the granulated slag was clarified. The influence of these factors on the density and grain size of the slag was confirmed by using various nozzles in the slag water granulation system. Neural network computation was applied to estimation of the density and grain size of granulated blast furnace slag. The influence of the water granulation conditions on the density and grain size predicted by neural network computation corresponded closely to the results of the laboratory-scale experiment. Based on the results of this research, we proposed a new slag granulation system and manufactured a high density, coarse blast furnace slag fine aggregate.